THE EFFECT OF NET INCOME, OPERATING CASH FLOW, INVESTMENT CASH FLOW, AND FUNDING CASH FLOW ON STOCK RETURNS (CASE STUDY OF ENTERPRISES REGISTERED IN THE LQ45 INDEX ON THE INDONESIA STOCK EXCHANGE 2018-2022) - Fariza Febriana; Nunung Aini Rahmah (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
Stock returns represent the profits gained from investing in stocks. Investors typically seek out shares of Enterprises that promise the highest returns. This investigation seeks to understand the relationship among net income, operating cash flow, investment cash flow, and funding cash flow, and how they affect stock returns. The study focuses on Enterprises registered on the Indonesia Stock Exchange under the LQ45 index from 2018 to 2022. Utilizing purposive sampling, data was collected from 23 Enterprises over a five-year period, outcoming in 115 samples. Secondary data was analyzed using multiple regression analysis. The outcomes reveal that net income does not significantly influence stock returns, while operating cash flow and funding cash flow positively effect stock returns. However, investment cash flow does not exhibit a significant effect on stock returns.